Leposternon microcephalum: Predation - Silva Guedes Folly, Henrique (2024)
Leposternon microcephalum is a terrestrial amphisbaenid found in open and semi-open habitats in Bolivia, Paraguay, Argentina, Uruguay, and Brazil (Pérez and Ribeiro 2008. Check List 4:291–294). They are reported to be common prey for snakes (e.g., Marques and Sazima 1997. Herpetol. Nat. Hist. 5:88–93; Caramaschi and Niemeyer 2012. Herpetol. Notes 5:429–430) and a wide variety of raptors and wading birds such as Amadonastur lacernulatus (Rajão et al. 2013. Herpetol. Rev. 44:509–510), Cariama cristata (Folly et al. 2015. Herpetol. Notes 8:465–466), and most recently, Guira guira (Pimentel et al. 2023. Herpetol. Rev. 54:289–290). Here, we report a new bird predator, the Red-billed Curassow (Crax blumenbachii), preying on L. microcephalum from southeastern Brazil. At 0913 h on 22 September 2019, we observed a pair of Redbilled Curassows (Crax blumenbachii) feeding on an adult L. microcephalum (ca. 35 cm total length) in the Reserva Particular do Patrimônio Natural (RPPN) Fazenda Macedônia, Ipaba Municipality, Minas Gerais, Brazil (19.3601°S, 42.39309°W; WGS 84; 232 m elev.). The birds were foraging along the banks of the Rio Doce, and the male held the lizard in its bill and repeatedly struck it against the ground for ca. 1 min until it appeared dead. Before the birds had a chance to eat the lizard, a group of people arrived nearby, and the pair abandoned their prey and flew 20 m away from the lizard. After 35 min the people left, and the pair returned, and the male swallowed the lizard whole (Fig. 1). To our knowledge this is the first report of Red-billed Curassows, an endangered and endemic species of the Brazilian Atlantic Forest, foraging and feeding on L. microcephalum. The known diet of Red-billed Curassows primarily consists of fruits, invertebrates, and leaves (Muñoz and Kattan 2007. Ornitol. Neotrop. 18:21–36), although other curassow species are known to feed on vertebrates (e.g., Santamaría and Franco 2000. Wilson Bull. 112:473–481; Muñoz and Kattan 2007, op. cit.), including one case of Amphisbaena alba (Costa and Santana 2024. Reptil. Amphib. 31:e21734). Since curassows mainly forage on the ground, they likely consume fossorial amphisbaenids more frequently than has previously been reported.